Предмет: Алгебра,
автор: Аноним
помогите решить один пример
Приложения:
Ответы
Автор ответа:
0
решение смотри на фотографии
Приложения:
Автор ответа:
0
(x-6y^2)/(2y)+3y
приведем к общему знаменателю
(x-6y^2+6y^2)/(2y) = x/(2y)
подставим значения
-8 / (2*0,1) = -8/0,2 = -40
приведем к общему знаменателю
(x-6y^2+6y^2)/(2y) = x/(2y)
подставим значения
-8 / (2*0,1) = -8/0,2 = -40
Приложения:
Похожие вопросы
Предмет: Математика,
автор: Popovayu320
Предмет: Математика,
автор: hajrullaevaziada
Предмет: Русский язык,
автор: inkaratas3
Предмет: Алгебра,
автор: zahlud
Предмет: Математика,
автор: yarabei